Kinetics and Mechanism of Hydrolysis of Mono-S-Butyl Phosphorothioate via Conjugate Acid Species - Shinde, C.P.; Patil (Mhala), R.; Shirdhonkar, Vaishali (Asian Journal of Chemistry, 2010)
Investigation of hydrolytic bond cleavage of mono-S-butyl phosphorothioate was carried out at 98ºC employing 5.0 X 10–4 mol dm–3 solution by using Allen's modified method of colorimetry.